Комп'ютерне моделювання в біомеханіці кровообігу - Кізілова, Наталія Миколаївна; Соловйова (Філіппова), Олена Миколаївна (Харківський національний університет імені В. Н. Каразіна, 2019)
У статті обговорюються можливості комп'ютерного моделювання для проведення розрахунків на детальних моделях кровоносної системи людини. Наведено короткий огляд існуючих математичних моделей і запропонована модель, яка дозволяє проводити розрахунки параметрів кровообігу – швидкості і тиску крові, переміщень стінок артерії – для складного дерева судин в реальному часі. На основі моделі проведено розрахунки параметрів кровообігу в моделі аорти (91 в'язкопружня трубка). Показано гарне відповідність результатів комп'ютерного моделювання вимірам тиску і швидкостей течії крові вздовж аорти.

The possibilities of computer modeling for numerical computations on detailed models of human circulatory system are discussed. A brief review of existing mathematical models is presented, and the model based on the axisymmetric incompressible Navier-Stokes equations for blood as a Newtonian fluid and the momentum equations for the incompressible viscoelastic arterial wall allowing real time calculations of blood circulation parameters – velocity and blood pressure, movements of the arterial walls – for a complex tree of blood vessels is proposed. The pulse waves propagation is investigated in the form of small perturbations. The geometrical model is based on the morphometric data of extraorgan (systemic) arteries performed on five corpses preparations. Depending on the individual geometry, a model of the middle tree containing ~ 1000 segments, which is the most detailed of the existing models of the tree of the human systemic arteries. Based on the model, the blood circulation parameters have been calculated in the aortic model (91 viscoelastic tubes). A good agreement between the results of computer simulation and the measurements of pressure and velocity of blood flow along the aorta has been shown. An analysis of the wave reflection coefficients revealed areas with abnormal values of friction on the wall and pressure oscillations that can lead to damage of the wall, the development of aortic aneurysm, stenosis of the renal arteries, and other pathologies. The proposed model can be used to calculate cases of pathology (narrowing, expansion, atherosclerotic plaques, and others) on an individual model of the patient’s aorta according to CT, MRT, ultrasound, etc., as well as for preliminary in silico modeling of vascular operations.
Computer modeling in mechanics of circulation
Keywords: пульсові хвилі; медична діагностика; кровоносна система; математичне моделювання; артерії; аорта; computer simulation; biomechanics; blood circulation; pulse waves; medical diagnostics